2016
DOI: 10.3171/2015.1.jns14603
|View full text |Cite
|
Sign up to set email alerts
|

Robotic intercostal nerve harvest: a feasibility study in a pig model

Abstract: The aim of this study was to report the feasibility of robotic intercostal nerve harvest in a pig model. A surgical robot, the da Vinci Model S system, was installed after the creation of 3 ports in the pig's left chest. The posterior edges of the fourth, fifth, and sixth intercostal nerves were isolated at the level of the anterior axillary line. The anterior edges of the nerves were transected at the rib cartilage zone. Three intercostal nerve harvesting procedures, requiring an average of 33 minutes, were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Miyamoto et al demonstrated the robotic technique on three porcine models in 2016. 35 Three ports were used, and the surgical time for harvesting three intercostal nerves (fourth, fifth, and sixth) was 40 minutes on average. There was no conversion to open approach, and no surgical complications reported.…”
Section: Peripheral Nerve Harvest (►Table 4)mentioning
confidence: 99%
“…Miyamoto et al demonstrated the robotic technique on three porcine models in 2016. 35 Three ports were used, and the surgical time for harvesting three intercostal nerves (fourth, fifth, and sixth) was 40 minutes on average. There was no conversion to open approach, and no surgical complications reported.…”
Section: Peripheral Nerve Harvest (►Table 4)mentioning
confidence: 99%
“…However, thoracoscopic intercostal nerve harvest still presents difficulties because endoscopic instruments are not capable of sufficient fine movement and interfere with surgeon precision. 3 , 8 …”
Section: Discussionmentioning
confidence: 99%
“…7 The possibility of robotic intercostal nerve harvesting has already been demonstrated in a pig model. 8 The purpose of this study was to report the feasibility of robot-assisted intercostal nerve harvesting in a clinical case.…”
Section: Introductionmentioning
confidence: 99%
“…1 Several of these early studies used animal models to demonstrate the feasibility of the epineural and neurotrophic repairs, and nerve harvesting techniques for use in brachial plexus repair. 8 40 41 Table 2 outlines the current published literature focusing on robot-assisted brachial plexus repair in human cadavers and subjects.…”
Section: Feasibility Studiesmentioning
confidence: 99%